A study on Norwegian offshore policy. Issue 3 (2nd July 2020) - Cho, Moon-Gyo
ABSTRACT: The world shipbuilding and shipping, offshore industries are experiencing a downturn due to oversupply, low economic growth, and low oil prices. Also, domestic shipbuilding and shipping industries are having difficult time due to bankruptcy of Hanjin shipping and restructuring of DSME. The market outlook for 2020 is still expected to be negative. In order to overcome the recession in the shipbuilding and shipping industry, Korean shipyards and shipping companies are making efforts to strengthen their competitiveness through aggressive investment inducement, restructuring, and merger and acquisition. Various countermeasures are being considered in connection with the government and academia. In order to overcome the current recession, the world's major maritime and offshore countries are developing a variety of offshore industry clusters based on government's strong policy support in addition to strengthening their own competitiveness and expanding their competitiveness based on competitive advantage. This is an ideal best practice. This study analyzes the Norwegian offshore policy and offshore industry clusters, one of the most representative maritime powers, and provides data for establishing policies that will lead to sound and continuous development of Korean shipbuilding, shipping, and offshore industries based on this analysis.